2021
DOI: 10.3390/jcdd8040043
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Functional Hierarchy of Pacemaker Clusters in the Sinoatrial Node: New Insights into Sick Sinus Syndrome

Abstract: The sinoatrial node (SAN), the primary pacemaker of the heart, consists of a heterogeneous population of specialized cardiac myocytes that can spontaneously produce action potentials, generating the rhythm of the heart and coordinating heart contractions. Spontaneous beating can be observed from very early embryonic stage and under a series of genetic programing, the complex heterogeneous SAN cells are formed with specific biomarker proteins and generate robust automaticity. The SAN is capable to adjust its pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 116 publications
1
19
0
1
Order By: Relevance
“…This is consistent with a study in isolated SAN cells from rabbit HF model of pressure and volume overload, which concluded that SAN Ca 2+ cycling properties are conserved despite bradycardic effects (Verkerk et al, 2015). However, the latest study did not take into account the presence of hierarchical pacemaker clustering within the SAN that might be modified in HF (Sanders et al, 2004;Lang and Glukhov, 2021). Preliminary data from our group, using TACinduced HF in the mouse indicate impairment of "Ca 2+ clock, " characterized by slower spontaneous [Ca 2+ ] i transients, as well as less frequent and smaller Ca 2+ sparks, supported by a mechanism including depression in the CaMKII signaling pathway (Xue et al, 2020).…”
Section: Ryr2 and Sinus Node Dysfunctionsupporting
confidence: 85%
“…This is consistent with a study in isolated SAN cells from rabbit HF model of pressure and volume overload, which concluded that SAN Ca 2+ cycling properties are conserved despite bradycardic effects (Verkerk et al, 2015). However, the latest study did not take into account the presence of hierarchical pacemaker clustering within the SAN that might be modified in HF (Sanders et al, 2004;Lang and Glukhov, 2021). Preliminary data from our group, using TACinduced HF in the mouse indicate impairment of "Ca 2+ clock, " characterized by slower spontaneous [Ca 2+ ] i transients, as well as less frequent and smaller Ca 2+ sparks, supported by a mechanism including depression in the CaMKII signaling pathway (Xue et al, 2020).…”
Section: Ryr2 and Sinus Node Dysfunctionsupporting
confidence: 85%
“…A shift in the leading pacemaker site with electrical stimulation of extracardiac inputs or during pharmacologic activation of autonomic receptors has been demonstrated in a variety of mammals (Opthof, 1988;Boyett et al, 2000;Lang and Glukhov, 2021), including rabbit (West, 1955;Toda and West, 1967;Bouman et al, 1968;Toda, 1968;Toda and Shimamoto, 1968;Spear et al, 1979;Mackaay et al, 1980;Shibata et al, 2001;Lang et al, 2011). In general, sympathetic stimulation tends to shift the leading pacemaker site superiorly, while parasympathetic Thollon et al, 1994Thollon et al, , 2007Bucchi et al, 2007;Yaniv et al, 2012Yaniv et al, , 2013Yaniv et al, , 2014 Noma et al, 1983;Dennis and Williams, 1986;Denyer and Brown, 1990;Leitch et al, 1995;Nikmaram et al, 1997;Zhang and Vassalle, 2000;Bogdanov et al, 2006;Thollon et al, 2007 I Ca,T Nickel 165 µM* −10% 40 -100 µM −14 -−18% Hagiwara et al, 1988;Satoh, 1995 Kawai et al, 1981;Senges et al, 1983;Satoh and Tsuchida, 1993;Masumiya et al, 1997;Budriesi et al, 1998;Bogdanov et al, 2006 RyR Ryanodine 1 µM −45% 1 -3 µM −14 -−50% Hata et al, 1996;Satoh, 1997;Bogdanov et al,...…”
Section: Leading Pacemaker Shift With Vagal Nerve Stimulationmentioning
confidence: 99%
“…The heart consists of two different kinds of myocytes, i.e., the working or forceproducing cardiac myocytes found in the atrial and ventricular chambers, and the nodal and conducting myocytes forming the cardiac conduction system (CCS). The CCS spontaneously generates and propagates electrical activity to trigger the synchronous and consecutive contraction of the atrial and ventricular chambers [1,2]. Atrial and ventricular myocytes are characterized by the presence of stable resting membrane potential, while CCS myocytes are characterized by spontaneous diastolic depolarization.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial and ventricular myocytes are characterized by the presence of stable resting membrane potential, while CCS myocytes are characterized by spontaneous diastolic depolarization. During each cardiac cycle, myocytes of the sinoatrial node (SAN) are the fastest to depolarize and first to generate action potential [1]. From the SAN, the electrical activation spreads to the atrial myocardium and subsequently to the ventricular chambers via the atrioventricular node (AVN).…”
Section: Introductionmentioning
confidence: 99%